Frameworks for ethics in public health - Jennings, Bruce (Acta Bioethica, 2003)
This paper constructs a conceptual framework for the normative study of public health. It argues that to develop discussions of ethics in public health without paying attention to the broader theoretical and ideological context of public health controversies and social conflicts will be of limited value. In defining that context, the author distinguishes three main types of ethical theory-utilitarianism, contractarianism, and communitarianism; and several varieties of political theory -liberal welfarism, liberal egalitarianism, libertarian liberalism, deliberative democracy, civic republicanism, and cultural conservatism. The meanings and interconnections of these theory formations are discussed. Illustrations to particular public health programs and issues are given. The paper also distinguishes four different types of applied ethical discourse in public health-professional ethics, advocacy ethics, applied ethics, and critical ethics. Each of these modes of ethics is important, but the development of work in critical ethics is the most important priority within the normative study of public health at present.